Kerjasama Guru Kelas dan Orangtua dalam Meningkatkan Minat Belajar Siswa Kelas V Pada Masa Pandemi Covid-19 - Eriyani; Nuraini; Dewi Ferawati (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
The purpose of this study is to find out: 1) What is the form of collaboration between teachers and parents in increasing interest in learning in fifth grade students at MIS Ikhlashul Amal Sebawi for the 2020/2021 academic year? 2) What are the supporting and inhibiting factors of teacher and parent collaboration in increasing interest in learning in fifth grade students at MIS Ikhlashul Amal Sebawi for the 2020/2020 academic year? This study uses a qualitative approach with the type of field research while the data collection techniques used are observation, interviews and documentation based on primary sources in the field, and secondary sources in the form of books or scientific research papers related to this research. The data analysis techniques used are data collection analysis, data reduction, data display, verification or drawing conclusions. Based on the results of the study, it can be concluded that: 1) the form of collaboration between teachers and parents in increasing the interest of fifth grade students at MIS Ikhlashul Amal Sebawi for the 2020/2021 academic year is by guiding children's learning at home, giving assignments, preparing learning materials, methods, facilities and infrastructure , to motivate students. 2) What are the supporting and inhibiting factors for the cooperation of teachers and parents in increasing the learning interest of fifth grade students at MIS Ikhlashul Amal Sebawi for the 2020/2021 academic year, the factors that support children's health, interest and motivation, children's learning methods, harmonious families. Factors inhibiting parents' educational background, lack of parental attention, lack of cooperation between parents and teachers.